2019
DOI: 10.1175/jamc-d-17-0268.1
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Thermally Driven Circulations in the Pyrenees: Comparison of Detection Methods and Impact on Atmospheric Composition Measured at a Mountaintop

Abstract: The atmospheric composition measured at the Pic du Midi high-altitude observatory (2875 m MSL) in the French Pyrenees is frequently affected by upward transport of boundary layer air during anabatic circulations at different scales. The Pyrenean Platform for Observation of the Atmosphere (P2OA) includes two observatories located 28 km apart: at the Pic du Midi and at a low-altitude site (580 m MSL) located in the plain north of the mountain chain. From a 10-yr-long data series collected at P2OA, three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 72 publications
4
18
0
Order By: Relevance
“…In winter, FT-and PBL-influenced conditions occurred roughly 74% and 26% of the analyzed time, respectively, against 48% and 52% for summer, respectively. These results are broadly in agreement with the previous study by Hulin et al (2019) at PDM, which quantified around 47 % of the days as PBL-influenced over a 10 years period. The PBL-influenced coditions occured mostly around 15:00 UTC, consistent with the dynamics at mountain sites where plain-tomountain winds and along-valley winds become the strongest in the afternoon (Whiteman, 2000).…”
Section: Meteorology and Air Mass Classificationsupporting
confidence: 93%
See 1 more Smart Citation
“…In winter, FT-and PBL-influenced conditions occurred roughly 74% and 26% of the analyzed time, respectively, against 48% and 52% for summer, respectively. These results are broadly in agreement with the previous study by Hulin et al (2019) at PDM, which quantified around 47 % of the days as PBL-influenced over a 10 years period. The PBL-influenced coditions occured mostly around 15:00 UTC, consistent with the dynamics at mountain sites where plain-tomountain winds and along-valley winds become the strongest in the afternoon (Whiteman, 2000).…”
Section: Meteorology and Air Mass Classificationsupporting
confidence: 93%
“…PDM was found to have a low ABL-Topoindex, similar to other Alpine high altitude stations. PDM is thus a suitable site to study both the background lower free troposphere (FT) over long timescales and injection of air masses from the PBL (Hulin et al, 2019;Tsamalis et al, 2014;Fu et al, 2016;Marusczak et al, 2017). In this article the instrumentation and methodology are presented in section 2.…”
Section: )mentioning
confidence: 99%
“…In the winter half year, photochemical O 3 production was assumed to play a minor role at high-alpine sites because of the generally low solar irradiance and the weak thermally induced uplift. This argument is supported by the trajectory residence time statistics of Kaiser et al (2007), which demonstrated that the O 3 mixing ratio at European high-alpine sites was generally lower in winter if the air mass originated from lower altitudes, whereas in summer, this was often not the case.…”
Section: Principal Component Analysismentioning
confidence: 83%
“…Rather, we showed that the tracers affect the south‐facing basin sidewalls due to asymmetric thermal forcing, even at relatively high elevation (up to 2000 m asl) while pollutants have been emitted at 560 m asl. Similar dynamics have already been observed in the Austrian Inn Valley during a wintertime pollution episode (Gohm et al ., ; Harnisch et al ., ) and should be considered carefully since it may influence the atmospheric composition measured at high‐altitude stations (Bukowiecki et al ., ; Hulin et al ., ). At night, the downstream transport appears as a second effective mechanism of material transport, but it mainly concerns the Sallanches tracers while Passy tracers tend to accumulate within the central curved sector of the BASINlow volume.…”
Section: Tracer Transport In the Reference Simulationmentioning
confidence: 99%